Adapting and Examining the Factor Structure of the Self-Compassion Scale in Indonesian Version - Irfan Aulia Syaiful; Adiyo Roebianto (Jurnal Psikologi, 2020)
The study aimed to adapt and analyze the factor structure of the scale of self-compassion in the Indonesian language. The initial steps included back-to-back translation, focus group discussion and expert judgements. From this procedure, thirteen additional items were added to the original self-compassion scale. The thirty-nine final items were tested to 483 samples from three different groups (undergraduate students, young and adult, mid and late adult). Findings support self-compassion as total score and six sub scale score based on ESEM bi factor analysis. However based on the overall results, for Indonesia uses, the authors suggested the structure data of self-compassion scale is a hierarchical two-factors model with the final items of this scale are 35 items, where the two factors are positive aspect and negative aspect. The positive dimension had 0.901 of Cronbach’s Alpha reliability and the negative dimension had 0.913 of Cronbach’s Alpha reliability. The positive one consists of self-kindness, common humanity, and mindfulness. Meanwhile, the negative one consists of self-judgement, isolation, and over-identification.